Nonlinear stability analysis of eccentrically stiffened S-FGM imperfect plates resting on elastic foundations - Luu, Duc Trung (H. : ĐHQGHN, 2017)
This paper presents an analytical approach to investigate effects of elastic foundation and stiffeners on the nonlinear buckling behavior of eccentrically stiffened S-FGM imperfect plates subjected to mechanical loads. By using classical plate theory, Bubnov-Galerkin’s method and stress function, the close-form expressions of buckling loads and nonlinear post-buckling load-deflection curves of the S-FGM plates are determined.